Legal And Non-Legal Approach In Handling Traffic Accidents In Satlantas - Herlambang, Yulius Prasetyo; Djati, Arjuna Galih; Lail, Nabila Hidayatul; Faudina, Rachel Ika; Renanda, Shandya Alonso Eka; Pratama, Muhammad Javier (jurnal.unprimdn.ac.id, 2025)
Based on the circular of the National Police Chief number 8 of 2018 concerning the use of Restorative Justice in the assessment of criminal cases, restorative justice can be used at the stage of criminal case development. This normative-Empirical Legal Research uses the method of legislation and cases. One of the primary data collection methods is field and library studies. The purpose of this study was to examine the application of the law in the case of traffic accidents in the jurisdiction of the Magelang resort police and the factors that caused the case. The results of the study showed that the implementation of law enforcement in the case of traffic accidents in the jurisdiction of the Magelang Resort Police has not gone well. There are two factors that affect the delay in resolving traffic accident cases in the Magelang resort police jurisdiction, namely internal factors such as human resources, facilities and infrastructure, as well as the relationship between the police and other agencies, as well as external factors such as community factors, Jasa Raharja, and BPJS. Kata Kunci: Tindak Pidana, Kecelakaan Lalu Lintas, Keadilan Restorative Justice.